Analysis of the Availability of Public Facilities in Urban Areas and Its Impact on the Quality of Life of the Community Case Study of Medan City - Abdi Sugiarto; Wahyu Indah Sari (ISNU Nine-Star Multidisciplinary Journal, 2024)
This study aims to analyze the availability of public facilities in urban areas, especially Medan City, and its impact on the quality of life of the community. The methodology used includes field surveys and in-depth interviews with 200 respondents who are residents in various sub-districts in Medan. The results of the study indicate that the availability of public facilities, such as parks, health centers, and public transportation, have a significant effect on the quality of life of the community. Respondents who live in areas with good public facilities reported higher levels of life satisfaction compared to those who live in areas with limited facilities. The results of the study are new knowledge that lack of access to public facilities can cause health problems, increased stress, and low social participation. This study concludes that increasing the availability and quality of public facilities in Medan City is very important to improve the quality of life of the community as a whole. So this study can be used as a basis for taking further policies.